Pengaruh Bauran Pemasaran Terhadap Peningkatan Penjualan Premi Asuransi Pada PT Asuransi Reliance Palembang - Vivin Afini; Indah Mawarni; Arubina Bangsawan; Tutik Pebrianti (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2020)
This study aims to determine the effect of marketing mix on increasing the insurance premium at PT Asuransi Reliance Palembang. The marketing strategy used by the company has not maximized, it can be seen from the insurance premium sales which not reached the sales target. The samples in this study were the insurance customers of PT Asuransi Reliance Palembang as many as 72 respondents. The Method used in taking the sample was simple random sampling by using Slovin formula. The analytical method is descriptive qualitative analysis using simple linear regression formula with SPSS program. The results of testing the hypothesis showed that variable X (marketing strategy) has an efeect on variable Y (sale), i.e. variable in marketing mix (β) of 0,363 means that every 1 unit increase in marketing mix will increase sales of 0.363 and the results of hypothesis testing with t-test indicate that there is a significant influence between marketing mix on increasing sales insurance premium at PT. Reliance Palembang Insurance. Based on the marking mix variable, lack of promotion causes the sales target not achieved thus promotional services to customers must be improved so that insurance products can be more recognized and improve the relationship with the cooperative parties to create better service efforts. Providing higher insurance premium discounts and not detrimental to the company can be done to attract customers so that the expected target company sales can be achieved.